Penguatan Kompetensi Guru Melalui Pelatihan Perangkat Pembelajaran Tematik Integratif Berbasis Nilai-Nilai Budaya Sasak di SMP Negeri 1 Masbagik - Al Pansori, Muh. Jaelani; Rismawati, Lia; Pransisca, Made Ayu; Alim, Abdul; Marzuki, Ahmad Dedi; Sahabudin, Sahabudin (Al-Tafani: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2025)
This community service program aimed to enhance the competence of teachers at SMP Negeri 1 Masbagik in developing integrative thematic learning tools based on Sasak cultural values. The background of the activity stems from the limited use of local wisdom in classroom instruction, which leads to a disconnect between the teaching materials and the students’ cultural context. The program was conducted using a Participatory Action Research (PAR) approach over three days, involving stages of needs assessment, training, mentoring, classroom trials, and reflection. A total of 25 teachers participated and showed significant improvement in their pedagogical understanding and skills, as reflected in the increase of their average scores from 61.4 (pretest) to 83.6 (posttest). Participants successfully produced lesson plans, teaching modules, and student worksheets incorporating Sasak cultural values such as the spirit of cooperation (begibung), environmental preservation (ngayu-ayu), and politeness in daily language use. A limited classroom implementation showed that students responded positively and were more engaged in lessons linked to their local culture. This program demonstrates that integrating local cultural content into instructional design can improve the quality and contextual relevance of learning while strengthening students’ cultural identity. It is recommended that similar training be conducted on a regular basis, accompanied by the systematic development of local-based teaching materials.